Private life of deer [videorecording (DVD)] - McGillin, Howard (PBS Distribution, 2013)
From kitchen windows, they are spotted, nibbling away at gardens and shrubs. Once they retreat from view, where do the white-tailed deer go? Scientists outfit deer with night vision cameras and GPS tracking equipment that reveal the hidden world of white-tailed deer in a whole new light, allowing to see them not as common backyard creatures, but as intelligent, affectionate family members.